CONTEMPORARY ROMANIAN HISTORICAL FICTION AS A MEDIATING TRANSISTOR OF THE “ZEMIPERIPHERY” - BAKO, Alina (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Contemporary Romanian Historical Fiction as a Mediating Transistor of the “Zemiperiphery”. Historical fiction, characterized by its ambivalence between political instrumentalization and fidelity to the real referent, emerges as a vector of transnational connectivity, translating (semi)peripheral narrative scenarios into the language of the global core. In the post-1990 Romanian context, this dynamic acquires particular salience through the lens of “zemiperiphery”, which, as Stephen Shapiro contends, operates as a “transistor” (2024, 54) amplifying the subaltern voice, otherwise inaudible to the core without its mediation. Post-1990 Romanian historical fiction, through its recourse to universal historical themes – emblematic figures, conflicts, and conquests – functions as a neohermetic channel (Braga 1995) of transculturation, liberating historical discourse from past ideological constraints and integrating it into the global networks of the publishing market. This process, underpinned by an aesthetics of “hyperconnectivity” (Deckard, Niblett & Shapiro 2024), enables the Romanian zemiperiphery to negotiate tensions between the local and the global, generating a hybrid cultural memory. By transgressing national boundaries and recontextualizing narrative, Romanian historical fiction constitutes a node of cultural flow, asserting a dynamic identity in dialogue with transnational networks. The theoretical framework is applied to a diverse range of historical fictions, selected for their distinct conceptual approaches and narrative strategies. These works exemplify different ways in which authors such as Răzvan Rădulescu, Constantin Țoiu, Doina Ruști, Constanța Vintilă-Ghițulescu, Filip Florian, and Octavian Soviany interpret and reimagine history. REZUMAT. Ficțiunea istorică românească contemporană ca un transmițător mediator al „zemiperiferiei”. Ficțiunea istorică, marcată de ambivalența între instrumentalizarea politică și fidelitatea față de referentul real, se afirmă ca un vector de conectivitate transnațională, traducând scenarii narative (semi)periferice în limbajul centrului global. În contextul românesc post-1990, această dinamică capătă o relevanță aparte prin prisma „zemiperiferiei”, care, conform lui Stephen Shapiro, funcționează ca un „tranzistor” (2024, 54) ce amplifică vocea subalternului, invizibilă centrului fără medierea sa. Ficțiunea istorică românească post-1990, prin recursul la teme istorice universale – figuri emblematice, conflicte și cuceriri –, devine un canal „neohermetic” (Braga 1995) de transculturare, eliberând discursul istoric de constrângerile ideologice ale trecutului și integrându-l în rețelele globale ale pieței editoriale. Acest proces, susținut de o estetică a „hiperconectivității” (Deckard, Niblett & Shapiro 2024), permite „zemiperiferiei” românești să negocieze tensiunile dintre local și global, generând o memorie culturală hibridă. Prin transgresarea frontierelor naționale și recontextualizarea narativă, ficțiunea istorică românească se constituie ca un nod de flux cultural, afirmând o identitate dinamică în dialog cu rețelele transnaționale. Cadrul teoretic este aplicat unui spectru divers de ficțiuni istorice, selectate pentru abordările lor conceptuale distincte și strategiile narative. Aceste opere exemplifică diferite moduri în care autori precum Răzvan Rădulescu, Constantin Țoiu, Doina Ruști, Constanța Vintilă-Ghițulescu, Filip Florian și Octavian Soviany interpretează și reimaginează istoria. Cuvinte-cheie: proza istorică, metaficțiune, zemiperiferie, model. Article history: Received 28 June 2025; Revised 17 August 2025; Accepted 29 August 2025; Available online 24 September 2025; Available print 30 September 2025